Radiolucent lines and revision risk in total knee arthroplasty using the conventional versus the Attune S+ tibial baseplate: results of a multicentre observational study - Smolle, Maria A.; Keintzel, Maximilian; Staats, Kevin; Böhler, Christoph; Windhager, Reinhard; Koutp, Amir; Leithner, Andreas; Donner, Stefanie; Reiner, Tobias; Renkawitz, Tobias; Sava, Manuel-Paul; Hirschmann, Michael T.; et al. (The bone & joint journal, 2024)
Radiolucent lines and revision risk in total knee arthroplasty using the conventional versus the Attune S+ tibial baseplate
Gesehen am 19.05.2025